THE LIBRARY OF THE FREE UNIVERSITY OF BERLIN. ENVIRONMENTAL FRIENDLINESS AS A RESPONSE TO MODERN CHALLENGES - STEPANIUK, Olena L.; KYRPYTA, Tamara V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2021)
Objective. The article deals with the functional organisation and design of the Free University Library in Berlin, which has become not only an information centre, but also a centre for supporting research, supporting and providing education and training with a green space. Methods. The article is the result of the thorough study of the Internet resources about “green” libraries and the Philological Library of the Free University of Berlin. Conclusion.The library is an example of how to implement the philosophy of sustainability in all processes of the organisation's life, without detracting from the importance of scientific and information support for the teaching and research process. Results. The article was an attempt to describe the ways in which modern technologies go hand in hand with resource-saving policy, which could be implemented in the university libraries ofUkraine.